Gender Equity Perceptions Among School-Going Adolescents: A Mixed-Methods Comparison Amongst Tribal and Non-Tribal Rural Areas of an Eastern State in India - Lahiri, Arista; Jha, Sweety Suman (Frontiers in Sociology, 2022)
Introduction: Gender equity is an important social determinant of population health. There are very few studies in the Indian context in this regard, and even less regarding the diversity in tribal-dominated and non-tribal regions. The current study was conducted to assess and compare the perceptions of adolescents going to selected schools of tribal-dominated and non-tribal rural areas in West Bengal, India, regarding gender equity. It also explored the teacher’s perceptions on gender equity in an attempt to contextualize the students’ perceptions. Methods: A mixed-methods study was conducted with a convergent parallel design in two co-education schools, each from tribal-dominated and non-tribal rural areas. In the quantitative survey total of 828 adolescents aged 14—19 years participated. The qualitative component involved 26 in-depth interviews (IDIs) with the selected teachers. Results: Overall, the respondents from tribal area had a better perception regarding the equitable privilege of independence among genders, equity in decision roles, and especially financial decision roles of women. Perceptions related to girls access to education were better among the boys from non-tribal area than their counterparts from tribal area. The non-tribal respondents had a more inadequate perception regarding women’s limited role. In general, the respondents perceived favorably against gender dominance. The teacher’s perceptions in the context were mostly concordant, with some exceptions, e.g., regarding dominance and violence-related issues, the teachers perceived differently, contrasting the better perceptions exhibited by the students. Conclusion: The teachers’ perceptions showed strict reliance on the deep-rooted social norms that can be taken up for behavior change interventions. Better perceptions from the tribal areas are an opportunity to further enhance on gender equity. The boys’ perceptions can still be improved more in favor of gender equity.